Implementation Early of Initiation Breastfeeding (EIB) by Health Workers in the Maternity Room of 'Aisyiyah Ponorogo General Hospital During Covid-19 Pandemic - Dian Meilani Saputra; Byba Melda Suhita; Ratna Wardani; Nurdina (Journal Of Nursing Practice, 2023)
Background: Early of initiation breastfeeding (EIB) can reduce the Infant Mortality Rate (IMR) and Maternal Mortality Rate (MMR). The COVID-19 pandemic reduced early initiation of breastfeeding activities. As a result of the COVID-19 pandemic, access to essential services such as breastfeeding counseling in hospitals has been disrupted. Purpose: The purpose of this study is that researchers want to examine the implementation of the EIB by health workers in the maternity room of "Aisyiyah Ponorogo" General Hospital during the COVID-19 pandemic. Methods: The research used was qualitative with a case study design. The social situation in this study was delivery support health workers in the Maternity Room and Perinatology Room with informants consisting of five implementing midwives and six implementing nurses. The data collection process was carried out until the data collected experienced data saturation. Data validity was tested using source triangulation, namely patients who gave birth at "Aisyiyah Ponorogo" General Hospital. Results: EIB at 'Aisyiyah Ponorogo General Hospital has always been applied to newborns since 2010 and underwent adjustments during COVID-19 pandemic. The EIB was not implemented due to several conditions which made it impossible. Supporting factors for the implementation of early initiation of breastfeeding are the number and ability of health workers and the facilities available from both the hospital and the patient's family. The obstacle in this study is the perinatology room which is located far away so that the nurses in the perinatology department have difficulty carrying out several tasks at once which will cause a discrepancy in the duration of EIB implementation. Conclusion: Collaboration between the hospital, health workers, and the community is needed in an effort to increase the implementation of EIB. Starting from the existence of policies from the Hospital, the ability of health workers and the willingness of the community to improve the implementation of EIB.